The hydromedusae and water masses of the Indian Ocean - D. Navas-Pereira; M. Vannucci (Brazilian Journal of Oceanography, 1991)
This analysis of distribution and abundance of species of Hydromedusae completes a report (Vannucci & Navas, 1973b) on the ecology of Indian Ocean Hydromedusae based on the zooplankton collected during the International Indian Ocean Expedition (IIOE). Distribution and abundance are taken here to be the ecological expression of variability of species in space and time. The aim was to identify the biological signature of below surface water masses that cannot be identified by remote sensing techniques. Selected species were taken as biological units, the oceanic water masses as defined by their T-S and T-O2 diagrammes were taken as the non biological units. Taken together they define different ecosystems of the Indian Ocean. About 45,000 specimens of hydromedusae taken at 480 stations were sorted from 900 plankton samples and all specimens were determined and counted. Several hauls, mostly stratified, were taken with closing nets, but not all contained hydromedusae. The distribution of each species was studied in relation to water salinity, temperature and dissolved oxygen; the limits of ecological tolerance and preference were defined by the environmental characteristics of the layers sampled by the nets and are given for each species. These can be grouped as follows: 1. Deep water species, cold tolerant, often eurytopic; 2. Antarctic species, cold loving, usually stenothermal with preference for low salinity; 3. Indian Ocean Central Water species, with preference for temperature lower than 19ºC and salinity not much higher than 35%o, usually found at sub-surface or intermediate depths, they may spread into the Arabian Sea and Bay of Bengal in surface layers; 4. Indian Ocean Equatorial System species, warm tolerant, usually prefer comparatively low salinity, high temperature and high oxygen content; 5. Bay of Bengal Surface Water species, found in surface layers of the Bay, with preference for low salinity, high temperature and high oxygen content; 6. Arabian Sea Surface Water species prefer very high salinity and high temperature; 7. Rare species. Some immigrants from the Mediterranean Sea are described and many species were found to be tolerant of dissolved oxygen content as low as 0.2 ml/1. Numerous individuals of many species were found to agglomerate at boundary layers. Esta análise da distribuição e abundância de hidromedusas é complementar ao relatório sobre a ecologia das hidromedusas do Oceano Índico, baseado no material coletado durante a Expedição Internacional do Oceano Índico. A distribuição e abundância são consideradas como a expressão ecológica da variabilidade espacial e temporal das espécies. O objetivo era identificar a assinatura biológica de massas d'água subsuperficiais, que não podem ser identificadas através de técnicas de sensoriamento remoto. Espécies selecionadas foram consideradas como unidades biológicas, e as massas d'água, definidas pelos seus diagramas T- S e T-O2, como unidades abióticas; em conjunto, definem os diferentes ecossistemas do Oceano Índico. Cerca de 45.000 exemplares de hidromedusas coletados em 480 Estações foram separados de 900 amostras de plâncton, sendo todos contados e examinados. Diversos arrastos, principalmente estratificados, foram efetuados com redes de fechamento, mas nem todos continham hidromedusas. A distribuição de cada espécie foi estudada em relação a salinidade, temperatura e teor de oxigênio dissolvido na água; os limites de tolerância ecológica e preferências foram definidos pelas características ambientais das camadas amostradas pelas redes,sendo dadas para cada espécie. Essas espécies podem ser agrupadas da seguinte forma: 1. Espécies de águas profundas, preferindo baixas temperaturas, geralmente euritópicas; 2. Espécies antárticas, tolerando baixas temperaturas, geralmente estenotérmicas, preferindo baixa salinidade; 3. Espécies da Água Central do Oceano Índico, preferindo temperaturas inferiores a 19ºC e salinidade não muito superior a 35%o, geralmente encontradas em profundidades subsuperficiais ou encontradas em profundidades subsuperficiais ou intermediárias, podendo se dispersar para o Mar Arábico ou para a Baía de Bengala, nas camadas superficiais; 4. Espécies do Sistema Equatorial do Oceano Índico, tolerando temperaturas elevadas, preferem geralmente salinidade relativamente baixa, temperatura e teor de oxigênio elevados; 5. Espécies da Água Superficial da Baía de Bengala, encontradas nas camadas superficiais da Baía, preferindo baixa salinidade, temperatura e teor de oxigênio elevados; 6. Espécies da Água Superficial do Mar Arábico, preferindo alta salinidade e alta temperatura; 7. Espécies raras. Foram descritos alguns imigrantes do Mar Mediterrâneo, e verificou-se que muitas espécies toleram teores de oxigênio dissolvido tão baixos quanto 0.2 ml/l. Muitos indivíduos de diversas espécies costumam aglomerar-se em camadas de discontinuidade entre massas d'água.